Jak dzieci/młodzież z głębszą niepełnosprawnością intelektualną kodują formacje słowotwórcze (na przykładzie kategorii nazw narzędzi) - MARCINIAK-FIRADZA, RENATA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Renata Marciniak-Firadza, Coding of word formation structures by children/adolescents with deeper intellectual disability (on the example of the category of the tool names), Interdisciplinary Contexts of Special Pedagogy, No. 22, Poznań 2018. Pp. 215–235 Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.13 Word formation plays an important role in the child’s linguistic and cognitive development, because the ability to interpret word formation structures and active use of the knowledge of derivation rules are the most important manifestations of linguistic competence at the lexical level. The aim of the article is a linguistic interpretation of selected names of tools obtained from children and adolescents aged 6–19 with diagnosed moderate and severe intellectual disability.. In the article, the author would like to draw attention first of all to the existence of word-formation structures in the linguistic awareness of children / adolescents and to the fact whether newly formed words are created in accordance with word-formation patterns existing in the Polish language or they diverge from these patterns.